The Relationship Between Nutritional Status and Age at Menarche Among Adolescent Girls at SD Islam Al Azhar 19 Sentra Primer and SMP Islam Al Azhar 22 Sentra Primer - Alifia Fakhreza, Najwa; Hastuti Andayani, Sri; Herawaty, Tuty (Jurnal Indonesia Sosial Sains, 2026)
Menarche, the first menstruation, is a key indicator of biological maturity in girls. The age at menarche varies due to factors such as genetics, environment, physical activity, socioeconomic conditions, and nutritional status. Proper nutrition is crucial for sexual maturation because it affects reproductive hormones. Poor nutrition can delay menarche, whereas overnutrition or obesity may lead to earlier menarche due to increased estrogen levels associated with higher body fat. This research aims to assess the relationship between nutritional status and age at menarche among students at SD Islam Al Azhar 19 Sentra Primer and SMP Islam Al Azhar 22 Sentra Primer. This analytical-descriptive study used a cross-sectional approach with 211 respondents selected through purposive sampling. Nutritional status was measured using anthropometric data (height and weight) and body mass index (BMI) calculation. Age at menarche was obtained through structured interviews. Statistical analysis was conducted to test the relationship between nutritional status and age at menarche, with significance set at p < 0.05. Most respondents had normal nutritional status, and the majority experienced menarche between the ages of 10–11 years. Statistical analysis revealed a significant relationship between nutritional status and age at menarche (p < 0.001), with normal nutritional status correlating with menarche at expected physiological ages. A significant relationship exists between nutritional status and age at menarche. Adequate nutrition is vital for timely menarche, and monitoring nutritional status while promoting balanced diets is essential for supporting adolescent growth, development, and reproductive health.